Research and evolution of the semantics of the "digital competencies" category in organizations - Kharchuk, Viktoriya; Zakorchemna, Olha (Management and Entrepreneurship: Trends of Development, 2026)
This article aims to examine the theoretical basis of the semantics of the category of “digital competencіes”, to trace the evolution of views on understanding this concept, and to outline distinctive approaches and features in the authors’ scientific works related to the interpretation of the phenomenon under study. The paper employs an analysis, synthesis, and comparison of content through the lens of three focuses – the research, regulatory, and applied fields. The latter is due to the need to take into account the peculiarities of organisations' activities, and to further develop the categorical and conceptual apparatus that addresses urgent challenges and opportunities in the digital era. It was found that, in the research field, the term is used in the singular as a set of relevant structural elements; in the regulatory and applied fields, in the plural, as an integral ability with a special focus on the use of digital tools. Based on the obtained results, we suggest that the given phenomenon has a multifaceted nature that can be studied holistically using the three outlined focuses. The article justifies the need to use the term "digital competencу" when it comes to its use by organisations, in the plural, as a support for the legal and scientific unification of domestic achievements with generally recognised international frameworks and research. As a result of the analysis, the category of "digital competencies" is defined as a complex and dynamic system of knowledge, skills, abilities, and attitudes of employees of the organisation that arises when using digital tools, producing digital content, and interacting with the latest digital models and technologies.JEL Classification: M12, M15, O15.